Urbanization and other factors affecting crime an empirical analysis for the Philippines (1980-2012). - Cabangal, Jaifreed; Ano, Joselito Z, Jr. (2015.)
The world regards crime as a function eependent on the performance of law enforcement.
Research Project (Undergraduate, Bachelor of Science in Economics) College of Arts and Sciences, University of the Philippines in the Visayas.
Keywords: Crimes -- Urban